The New Paradigms in Clinical Research: From Early Access Programs to the Novel Therapeutic Approaches for Unmet Medical Needs - Scavone, Cristina; di Mauro, Gabriella; Mascolo, Annamaria; Berrino, Liberato; Rossi, Francesco; Capuano, Annalisa (Frontiers in Pharmacology, 2019)
Despite several innovative medicines were worldwide approved in recent years, there are still therapeutic areas for which unsatisfied therapeutic needs persist. For example, high unmet clinical need was observed in patients diagnosed with type 2 diabetes mellitus, hemophilia as well as in specific age groups, such as the pediatric population. Given the urgent need to improve the therapy of clinical conditions for which unmet clinical need is established, clinical testing and approval of new medicines are increasingly carried out thought accelerated authorization procedures. Starting from 1992, the Food and Drug Administration and the European Medicines Agency have supported the so-called Early Access Programs. Such procedures, which can be based on incomplete clinical data, allow an accelerated marketing authorization for innovative medicines. The growth in pharmaceutical research has also resulted in the development of novel therapeutic approaches, such as biotech drugs and Advanced Therapy Medicinal Products, including new monoclonal antibodies for the treatment of asthma, antisense oligonucleotides for the treatment of Duchenne muscular dystrophy and spinal muscular atrophy and new anticancer drugs that act on genetic biomarkers rather than any specific type of cancer. Even though Early Access Programs and novel therapeutic approaches have carried huge novelties and benefits for public health, their implementation is limited by several challenges, including the high risk of safety-related label changes for medicines authorized through accelerated procedure, the high costs, and the reimbursement and access concerns. In this context, regulatory agencies should provide the best conditions for the implementation of the described new tools.